Epidural versus subcutaneous administration of alfentanil for the management of postoperative pain - Chrubasik, Joachim; Chrubasik, Sigrun; Ren, Yungong; Schulte Mönting, Jürgen; Martin, Eike (Anesthesia & analgesia, 1994)
This study was designed to compare the efficacy and serum concentrations of alfentanil given subcutaneously (SQ) or epidurally (EPID) for treatment of postoperative pain. Following abdominal surgery, patients (n = 12) were randomly assigned to receive double-blind SQ or EPID alfentanil over 24 h via the allocated route (1 mg along with 0.2 mg/h and 0.2-mg boluses on demand) and saline via the other route of administration using a patient-controlled analgesic (PCA) delivery system. Significantly less EPID alfentanil produced better quality analgesia and fewer side effects than SQ alfentanil. The fact that EPID analgesia was maintained with serum alfentanil concentrations less than those producing systemic analgesia confirms the spinal site of the EPID alfentanil action.
Gesehen am 18.07.2024